Antioxidant Activity of Pastinaca sativa L. ssp. sylvestris [Mill.] Rouy and Camus Essential Oil - Jianu, Călin (Molecules, 2020)
In the last decade, there has been growing interest in the food industry in replacing synthetic chemicals with natural products with bioactive properties. This study’s aims were to determine the chemical composition and the antioxidant properties of the essential oil of Pastianica sylvestris. The essential oil was isolated with a yield of 0.41% (w/v) by steam distillation from the dried seeds and subsequently analysed by GC-MS. Octyl acetate (78.49%) and octyl hexanoate (6.68%) were the main components. The essential oil exhibited an excellent activity for the inhibition of primary and secondary oxidation products for cold-pressed sunflower oil comparable with butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT), which were evaluated using peroxide and thiobarbituric acid values. The antioxidant activity of the essential oil was additionally validated using DPPH radical scavenging (0.0016 ± 0.0885 mg/mL), and β-carotene-linoleic acid bleaching assays. Also, the amounts of total phenol components (0.0053 ± 0.0023 mg GAE/g) were determined.